The pharaoh key [compact disc, unabridged] - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J. Gideon Crew novel., 2018)
Fresh off a diagnosis that gives him only months to live, Gideon Crew--brilliant scientist, master thief, and intrepid adventurer--is on the trail of a centuries-old stone tablet that will either save his life or bring it to a sudden, shocking close.